Cooperative Spectrum Sensing Application Using RTL-Dongle Technology. - Urquiza Villalonga, David Alejandro; García Cotrina, Eduardo; Vistorte Salgado, Alejandro A.; Torres Gómez, Jorge; Lee García, David (Telemática, 2019)
Cognitive Radio (CR) systems have become a key paradigm for future wireless communications. Spectrum management efficiency is improved by CR strategies, which allows to Secondary Users (SUs) get opportunistic access to idle bands licensed to Primary Users (PUs). Opportunistic access is usually achieved through spectrum sensing (SS) techniques to identify spectrum holes. Detection performance of spectrum holes, given by probability of detection (Pd) and probability of false alarm (Pfa), is improved when cooperative scheme is implemented. Cooperative Spectrum Sensing (CSS) schemes require a Fusion Center (FC) to collect and merge SS results from SUs, then to have enhance performance. In this paper, we propose a C/C++ application based on Client/Server architecture for Cooperative Spectrum Sensing (CSS). RTL-Dongle device with Software Defined Radio (SDR) capabilities is used to implement SUs nodes. Local sensing is implemented on each node by using Energy Detector (ED) method provided itslower computational costs. Then, each individual SS results are transmitted to the FC according to centralized model of data report. FC data fusion is implemented by applying AND and OR parallel fusion rules. Finally, detection report is stored into .txt file for further processing. Application performance is evaluated by detecting a transmitted reference pilot tone using ICOM-IC7100 equipment. Obtained results confirm the improvement of Pd and Pfa values.